Court Responses to Batterer Program Noncompliance in the United States, 2005-2006 - Labriola, Melissa ([Verlag nicht ermittelbar], 2007)
The purpose of this study was to explore to what extent criminal courts nationwide are advancing the goal of accountability by imposing consequences on offenders who are noncompliant with a batterer program mandate. The study also sought to understand the goals that courts, batterer programs, and victim assistance agencies currently ascribe to batterer programs. In March 2005, a preliminary survey was sent to 2,445 batterer programs nationwide found through multiple sources. Preliminary survey results were analyzed, and a final sample of 260 communities or triads (courts, batterer programs, and victim assistance agencies) was selected. Respondents were asked to complete a Web-based survey in May 2006. Alternatively, respondents could request a hard-copy version of the survey. The variables in this study encompass community demographic information, the functions that court mandates to batterer programs serve, and the primary focus of the curriculum of batterer programs. Variables specific to batterer programs capture whether the program accepts court-mandated referrals only or volunteers as well, the length and duration of the program, possible reasons for noncompliance, and an approximate program completion rate. Variables related to the interaction between courts and batterer programs capture whether the court receives progress reports from the batterer program, and if so, when, and who receives them.